Addendum: Action potential propagation and block in a model of atrial tissue with myocyte–fibroblast coupling. (6th May 2021) - Mortensen, Peter; Gao, Hao; Smith, Godfrey; Simitev, Radostin D
Abstract: The analytical theory of our earlier study (Mortensen et al., 2021, Math. Med. Biol., 38, 106–131) is extended to address the outstanding cases of fibroblast barrier distribution and myocyte strait distribution. In particular, closed-form approximations to the resting membrane potential and to the critical parameter values for propagation are derived for these two non-uniform fibroblast distributions and are in good agreement with numerical estimates.